2013
DOI: 10.1148/radiol.12120499
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Contrast-enhanced MR Imaging of Carotid Atherosclerotic Plaque: Model Selection, Reproducibility, and Validation

Abstract: The Patlak model is most suited for describing carotid plaque enhancement. Correlation with histologic findings validated K(trans) as an indicator of plaque microvasculature, and the reproducibility of K(trans) was good.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
109
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(117 citation statements)
references
References 31 publications
6
109
0
2
Order By: Relevance
“…49 This technique has been shown to be highly reproducible and reliable. 33 Millon et al demonstrated that neovascularity is seen in up to 97% of areas with Gd enhancement on postcontrast images, whereas macrophage infiltration is seen in 87% of regions of Gd enhancement.…”
Section: 123mentioning
confidence: 99%
“…49 This technique has been shown to be highly reproducible and reliable. 33 Millon et al demonstrated that neovascularity is seen in up to 97% of areas with Gd enhancement on postcontrast images, whereas macrophage infiltration is seen in 87% of regions of Gd enhancement.…”
Section: 123mentioning
confidence: 99%
“…MRI also can assess the presence of neovasculature in carotid artery plaques [82][83][84][85]. A recent study by Gaens et al [85] showed that dynamic contrast-enhanced MR of carotid atherosclerotic plaques can assess plaque neovasculature and that the Patlak model is well-suited for describing carotid plaque enhancement; the authors found that the K(trans) is an indicator of plaque microvasculature (validated by histology) and that the reproducibility of K(trans) was good.…”
Section: The Plaque Neovascularizationmentioning
confidence: 99%
“…Among many biological targets implicated in plaque inflammation, macrophages and neovessels have gained broad interest because they are abundant and detectable by clinical imaging modalities such as 18 F-fluorodeoxyglucose (FDG) positron emission tomography (PET) and dynamic contrast-enhanced (DCE) MRI. [3][4][5][6] Increased metabolic activity measured as target-to-background ratio (TBR) is thought to indicate enhanced macrophage recruitment and activation. 3,7 In contrast, the transfer constant (K trans ) in DCE-MRI is considered to reflect microvessel density and permeability.…”
mentioning
confidence: 99%
“…3,7 In contrast, the transfer constant (K trans ) in DCE-MRI is considered to reflect microvessel density and permeability. 5,6 As 2 integral components of the inflammatory process, previous studies have suggested that cellular events, including macrophage recruitment and activation, and vascular adaptation, including angiogenesis and increased permeability, could affect each other during atherogenesis.…”
mentioning
confidence: 99%